1990
DOI: 10.1017/s0003356100005225
|View full text |Cite
|
Sign up to set email alerts
|

The nutritive value of fruits (pods with seeds) from four Acacia spp. compared with extracted noug (Guizotia abyssinica) meal as supplements to maize stover for ethiopian highland sheep

Abstract: Forty Menz rams weighing 20 to 22 kg and aged 13 to 18 months were individually offered 1·0 kg/day chopped maize stover and one of five supplements over a 70-day growth trial followed by a 10-day metabolism trial. The amounts of supplement offered were designed to supply 4·4 g nitrogen per day and with stover, sufficient nutrients to allow growth rates of 50 g/day. The control supplement, 80 g dry matter (DM) per day extracted noug (Guizotia abyssinica) meal, was compared with 194 to 212 g DM per day of fruits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 8 publications
2
23
3
Order By: Relevance
“…From our study, NDF levels varied between 438.4 and 621.7 g/kg DM among the different species. Wide variations in NDF levels in browse have been observed in other studies Tanner et al, 1990;Kaitho et al, 1997;Larbi et al, 1998;Maasdorp et al, 1999;Hove et al, 2001). The higher NDF levels recorded in our study could be due to the inclusion of petioles in the foliage of all species tested.…”
Section: Discussionsupporting
confidence: 73%
“…From our study, NDF levels varied between 438.4 and 621.7 g/kg DM among the different species. Wide variations in NDF levels in browse have been observed in other studies Tanner et al, 1990;Kaitho et al, 1997;Larbi et al, 1998;Maasdorp et al, 1999;Hove et al, 2001). The higher NDF levels recorded in our study could be due to the inclusion of petioles in the foliage of all species tested.…”
Section: Discussionsupporting
confidence: 73%
“…The values for phenolic compounds in this study were lower compared to that reported by Osuga et al [35]. Phenolic compounds are the largest single group of secondary plant compounds (SPCs), and total phenolics in plants can reach up to 40% of the dry matter [36]. In grasses, the major phenolic is lignin that is bound to all plant cell walls, and is a significant limiting factor in their digestion in the rumen [34].…”
Section: Anti-nutritive Substancescontrasting
confidence: 75%
“…Trees, especially those of the Acacia genus, are adapted to a low moisture environment (Timberlake et al, 1999) thus offer a reliable source of feed in the form of leaves and fruits. Many Acacias produce potentially nutritious fruits with up to 20% crude protein (Tanner et al, 1990;Kibon & Maina, 1993;Ncube & Mpofu, 1994;Mlambo et al, 2008), which could be used to supplement low quality roughage in the long dry season. However, anti-nutritional factors, such as tannins, are known to be a significant component of many browse tree species (Aganga & Mosase, 2001;Mlambo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%